ChemInform Abstract: 5‐Hydroxypent‐2‐enenitriles as Precursors Toward Dihydropyranones, Dienenitriles and Functionalized Naphthalenes. Issue 45 (14th October 2013) - Zhang, Xinying; Jia, Xuefei; Liu, Nan; Guo, Xiaojie; Song, Yunping; Fan, Xuesen
Abstract The treatment of a variety of 4‐hydroxypent‐2‐enenitriles with sulfuric acid at elevated temperature is described.